Usage of Complex Counting and Survey System in the Planning of Urban Public Transport System - Horváth, B. (Acta Technica Jaurinensis, 2011)
One of the main problems of planning urban public transport systems is the calculation of demand. The simplest way to solve this problem is to perform a detailed passenger counting and questioner. Through the project “Új Magyarország” TIOP 1.3.1 the Department of Transport at the Széchenyi István University has got a new complex system to support passenger counting and passenger surveys. This article summaries the need for such a system, the operation and the first experiences with it.